IMPROVING THE EFFECTIVENESS OF TREATING ORAL CHANGES CAUSED BY PSYCHOTROPIC DRUGS - Kaxxorovna, Rakhmonova Bakhora (PT. Antis International Publisher, 2025)
Objective: This study aimed to evaluate the effects of systemic hormone replacement therapy (HRT) on clinical and laboratory parameters of the oral cavity and salivary glands in women with surgically induced menopause. Methods: Seventy women aged 45 to 53 years with surgically induced menopause were examined. Thirty-four of these women received treatment to maintain dental health according to the traditional scheme, while thirty-six were additionally prescribed systemic HRT with transdermal gel “Estrogen” containing estradiol. A comparison group consisted of 34 premenopausal women. Hormonal status, dental condition indicators, and the properties and composition of mixed saliva were assessed. Cytological and microbiological studies of smears from the oral mucosa were conducted. Dynamic monitoring was performed preoperatively and at 3, 6, and 12 months post-surgery. Results: Women with surgically induced menopause, treated according to the traditional regimen, showed worsening clinical and laboratory indicators, including saliva quantity and quality, with signs of xerostomia, changes in the microbial landscape, and oral mucosal epithelium alterations. In contrast, women receiving HRT in addition to traditional treatment exhibited significantly less deterioration in these parameters. Novelty: This study reveals the positive effect of systemic hormone replacement therapy with transdermal estradiol on oral cavity health in women with surgically induced menopause, highlighting its role in mitigating adverse changes in the salivary glands and oral mucosa during early menopause.